Pengembangan Media Komik untuk Meningkatkan Kemampuan Membaca Siswa Sekolah Dasar - Siskawati, Yulia; Ramadan, Zaka Hadikusuma (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The research was carried out because educators did not use comics media at SDN 010 Kuantan Sako. The lack of student interest in learning caused some students to be slow to read properly and correctly. This research was carried out to make students who are dynamic and interested in starting to read carefully in the learning process, one of which is by making comic media. This research is development research (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The approach used is a qualitative approach and a quantitative approach that uses two methods of data collection: observation and interview. This research was conducted by testing the validity of 6 expert validators: two media validators, two language validators, and two material validators. The results of the media expert validity test are 95.31%, the linguist validity test is 92.18%, and the material expert validity test results are 89.06%, with a final average of 92.18%. So based on the comic media validity test, six validators showed valid results and were suitable for use in the learning process.